Differences in lung function and prevalence of pneumoconiosis between two kaolin plants. Issue 11 (November 1989) - Baser, M E; Kennedy, T P; Dodson, R; Rawlings, W; Rao, N V; Hoidal, J R
Abstract : To investigate the origin of differences in previously published pulmonary function studies of workers in kaolin plants in Georgia, spirometric and radiographic data collected in a cross sectional survey of two large plants were analysed. As compared with workers in plant 2, workers in plant 1 had a 2.7-fold greater prevalence of pneumoconiosis and a mean 0.361 decrement in adjusted forced vital capacity. Our previous finding that exposure to kaolin was not associated with a decrement in lung function may have resulted from failure to consider differences between the plants.